(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this essay, the French-Uruguayan playwright Sergio Blanco exposes the main references in the history of Western Ideas that support his writing process in works that he names as autofictional. Throughout the text, he discusses that, far from signifying a narcissistic desire for exposure, this autofictional exercise is a path of deep investigation into writing and creation.